Solanum dulcamara L. Berries: A Convenient Model System to Study Redox Processes in Relation to Fruit Ripening - Milica Milutinović; Đura Nakarada; Jelena Božunović; Miloš Todorović; Uroš Gašić; Suzana Živković; Marijana Skorić; Đurđa Ivković; Jelena Savić; Nina Devrnja; Neda Aničić; Tijana Banjanac; et al. (MDPI AG, 2023)
The present study provides, for the first time, a physicochemical and biochemical characterization of the redox processes associated with the ripening of Solanum dulcamara L. (bittersweet) berries. Electron Paramagnetic Resonance Spectroscopy (EPRS) and Imaging (EPRI) measurements of reactive oxygen species (ROS) were performed in parallel with the tissue-specific metabolic profiling of major antioxidants and assessment of antioxidant enzymes activity. Fruit transition from the mature green (MG) to ripe red (RR) stage involved changes in the qualitative and quantitative content of antioxidants and the associated cellular oxidation and peroxidation processes. The skin of bittersweet berries, which was the major source of antioxidants, exhibited the highest antioxidant potential against DPPH radicals and nitroxyl spin probe 3CP. The efficient enzymatic antioxidant system played a critical protective role against the deleterious effects of progressive oxidative stress during ripening. Here, we present the EPRI methodology to assess the redox status of fruits and to discriminate between the redox states of different tissues. Interestingly, the intracellular reoxidation of cell-permeable nitroxide probe 3CP was observed for the first time in fruits or any other plant tissue, and its intensity is herein proposed as a reliable indicator of oxidative stress during ripening. The described noninvasive EPRI technique has the potential to have broader application in the study of redox processes associated with the development, senescence, and postharvest storage of fruits, as well as other circumstances in which oxidative stress is implicated.